Evaluation of Seismic Performance and Effectiveness of Multiple Slim-Type Damper System for Seismic Response Control of Building Structures - David Kim; Eun Hee Sung; Kwan-Soon Park; Jaegyun Park (The Scientific World Journal)
This paper presents the evaluation of seismic performance and cost-effectiveness of a multiple slim-type damper system developed for the vibration control of earthquake excited buildings. The multiple slim-type damper (MSD) that consists of several small slim-type dampers and linkage units can control damping capacity easily by changing the number of small dampers. To evaluate the performance of the MSD, dynamic loading tests are performed with three slim-type dampers manufactured at a real scale. Numerical simulations are also carried out by nonlinear time history analysis with a ten-story earthquake excited building structure. The seismic performance and cost-effectiveness of the MSD system are investigated according to the various installation configurations of the MSD system. From the results of numerical simulation and cost-effectiveness evaluation, it is shown that combinations of the MSD systems can effectively improve the seismic performance of earthquake excited building structures.